Strategi Penguatan Karakter Mahasiswa Melalui Matakuliah Komunikasi dan Advokasi Kebijakan - Bambang Suprianto; Aria Mulyapradana (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Describing strategies for strengthening student character through communication and policy advocacy courses is the purpose of this research. This research uses qualitative descriptive. The subjects in this research are lecturers who teach communication and policy advocacy courses and students who have taken these courses at the Candradimuka College of Social and Political Sciences Palembang. The result of this research is that this course has been integrated with character education, but there needs to be development in RPS and there needs to be standardization in learning methods in order to improve the quality of character building of students who are taking the course and lecturers can also be role models for students both in attitude, speech and behavior delivered must show nationalism character in order to support optimal strengthening of student character.